2021
DOI: 10.1038/s41598-021-00381-9
|View full text |Cite
|
Sign up to set email alerts
|

The new SRS/FSRT technique HyperArc for benign brain lesions: a dosimetric analysis

Abstract: To evaluate the potential benefit of HyperArc (HA) fractionated stereotactic radiotherapy (FSRT) for the benign brain lesion. Sixteen patients with a single deep-seated, centrally located benign brain lesion treated by CyberKnife (CK, G4 cone-based model) were enrolled. Treatment plans for HA with two different optimization algorithms (SRS NTO and ALDO) and coplanar RapidArc (RA) were generated for each patient to meet the corresponding treatment plan criteria. These four FSRT treatment plans were divided into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Overall, HA demonstrated e cient delivery, rapid dose falloff, and high-quality treatment plans with coplanar and up to 3 noncoplanar arcs. Additionally, the automated HA treatment plan delivery in the SRS work ow increased physicians' con dence in managing small target lesions [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, HA demonstrated e cient delivery, rapid dose falloff, and high-quality treatment plans with coplanar and up to 3 noncoplanar arcs. Additionally, the automated HA treatment plan delivery in the SRS work ow increased physicians' con dence in managing small target lesions [12].…”
Section: Discussionmentioning
confidence: 99%
“…HyperArc (HA, Varian Medical System Inc., Palo Alto, CA, USA) is a novel isocentric-volumetric modulated arc radiotherapy (VMAT) technique explicitly developed for noncoplanar MLC-based stereotactic radiotherapy with automated optimization and delivery [10,11]. Good dosimetric distribution has made HA an attractive SRS technique for treating benign brain lesions [12]. This study aims to evaluate the feasibility of HA for TN by comparing it with the dose distribution of CyberKnife.…”
Section: Introductionmentioning
confidence: 99%
“…Calvo et al 6,7 . showed that dosimetrically comparable plans could be created regardless of whether the isocenter was in the target.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of HyperArc (HA) (Varian Medical System, Palo Alto, CA), an automated noncoplanar volumetric modulated arc therapy (VMAT) approach, has generated widespread discussion in the literature 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 on the topic of single‐isocenter stereotactic radiosurgery (SRS) and stereotactic radiotherapy (SRT) of multiple brain metastases. Treatments conducted with a single isocenter have the obvious advantage of reducing treatment time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation